ARTIKEL REVIEW: STUDI FITOKIMIA DAN FARMAKOLOGI BUAH JERUK NIPIS (Citrusaurantifolia s.) - Herta Meidya Nurhalita; Salsabilla Dhiya Atik Nuraini, Muhammad Rizky Imami, Alfi Dwi Seviah, Fitria Ayu Kusumaningtyas, Mar (CV. Adiba Aisha Amira, 2024)
The plant known as lime, or Citrus aurantifolia, has a history of medicinal uses. Since citric acid is the main component of limes, other ingredients include essential oils, calcium, potassium, phosphorus, iron, copper, and amino acids (tryptophan and lysine). Apart from that, one of the components of lime which is believed to have the most influence in preventing the development of bacteria is the chemical flavonoid. An article collection approach that has been adapted to the subject matter was used to create this research. to obtain related information regarding the pharmacological effects of lime fruit and phytochemical screening. Histochemical analysis of lime fruit shows that it contains phenols, terpenoids, alkaloids, flavonoids and tannins. In contrast, orange peel does not contain phenol. Antibacterial agents can be made from lime peel and leaves. This journal study concluded that lime leaf extract can inhibit Klebsiella oxytoca bacteria, while lime peel extract can inhibit P acnes bacteria.